The relationship between cortisol production rate and serial serum cortisol estimation in patients on medical therapy for Cushing's syndrome. - Trainer, P; Eastment, C; Grossman, A; Wheeler, M; Perry, L; Besser, G (1993)
OBJECTIVE: The aim was to determine the target range into which mean daily serum cortisol should be lowered in patients on medical therapy for Cushing's syndrome, using isotopically estimated cortisol production rates as 'gold standard'. DESIGN: Patients with Cushing's syndrome on medical treatment were given 12 ng of tritiated cortisol intravenously and a 24-hour urine collection was made in a single day. On the same day, serum cortisol was measured at 0900, 1200, 1500, 1800, 2100, and at 2400 h in in-patients. In addition, serum cortisol was measured at the same times as above in a group of healthy volunteers. SUBJECTS: Twenty-two patients on medical therapy for Cushing's syndrome were studied on a total of 29 occasions. In addition, serum cortisol profiles were obtained in 12 healthy volunteers. RESULTS: The median serum cortisol in patients with Cushing's syndrome was 400 (range 66-839) nmol/l, and in the healthy volunteers 178 (range 137-299) nmol/l. The median isotopic cortisol production rate in the patients with Cushing's syndrome was 84 mumol/24 h, range 10-343 (normal range 22-83) mumol/24 h. In the patients with Cushing's syndrome, the correlation of mean serum cortisol to cortisol production rate was +0.77 (P < 0.001). Normal rates were found when mean serum cortisol levels were between 150 and 300 nmol/l. CONCLUSIONS: The aim of drug therapy for Cushing's syndrome should be to lower the mean serum cortisol through the day into the range 150-300 nmol/l.